2012
DOI: 10.1177/0731948711435794
|View full text |Cite
|
Sign up to set email alerts
|

Note-Taking Techniques for Students With Disabilities

Abstract: This article provides a synthesis of note-taking research among students with learning disabilities or other high-incidence disabilities. A search of the professional literature between 1980 and 2010 yielded nine intervention studies, which were evaluated either in terms of effect size or percentage of nonoverlapping data. The studies examined three different notetaking techniques used by students during lectures and included 125 students of varying disabilities. Findings revealed that students who used note-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…We provided partial guided notes before class and allowed students to review the material, assisting with their ability to comprehend the material during the lecture to better remember and incorporate the material into long-term storage. 23 Providing partial guided notes decreases the amount of time students have to think about the information being presented or read and improve the overall organization, accuracy and completeness of their notes. 24 , 25…”
Section: Discussionmentioning
confidence: 99%
“…We provided partial guided notes before class and allowed students to review the material, assisting with their ability to comprehend the material during the lecture to better remember and incorporate the material into long-term storage. 23 Providing partial guided notes decreases the amount of time students have to think about the information being presented or read and improve the overall organization, accuracy and completeness of their notes. 24 , 25…”
Section: Discussionmentioning
confidence: 99%
“…Cognitivism-based inclusive education practices are implemented by applying different instructional approaches focused on learning activities, such as note-taking (Boyle & Rivera, 2012), underlining (Swanson, Orosco, & Lussier, 2014), summarizing (Wittrock & Alesandrini, 1990), writing to learn, outlining and mapping, and use of the PQ4R method (Slavin, 2009). The use of these instructional approaches has shown positive results among students with special needs in general education classrooms.…”
Section: Cognitivism-based Inclusive Education Practicesmentioning
confidence: 99%
“…In addition to self-testing, findings also lend support to the need for guided note-taking for these LLD students (for a review, see Boyle & Rivera, 2012). Research has demonstrated that note-taking during lectures is critical to understanding and retaining information (Kobayashi, 2005).…”
Section: Discussionmentioning
confidence: 50%